PROBLEMATIKA PEMBIAYAAN AKAD MUSYARAKAH DI BAITUL MAAL WAT TAMWIL FASTABIQUL KHAERAT MAKASSAR - Jabal Rahmat S; Musyfikah Ilyas; Basyirah Mustarin (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2023)
Abstrack Shows that from the data that the researcher got from BMT Fastabiqul Khaerat Makassar about the procedure for applying for financing after being compared with the existing theory. The financing application procedure applied by BMT Fastabiqul Khaerat can be said to be quite good, because it has been systematically arranged starting from file submission, survey process, assessment of 5C principles (Character, capacity, capital, collateral and condition). The problems that occur at BMT Fastabiqul khaerat are influenced by two factors, the first. Internal factors are factors that come from within the BMT itself. The second factor is External Factors, namely factors originating from outside the BMT, namely unfavorable economic conditions resulting in a decrease in people's purchasing power, failure of customer business, character of customers who are not trustworthy or dishonest in returning their obligations to BMT. While the strategy in Overcoming the Problems of Financing Musyarakah Contracts at BMT Fastabiqul Khaerat Makassar is rescheduling, Reconditioning, Settlement through guarantees BMT Fastabiqul Khaerat Makassar will temporarily confiscate the members' collateral because members are considered to have been negligent in returning the financing. Keywords: Baitul Maal Wat Tamwil, Financing, Musharaka contract.